Redefining indefinites - Dobrovie-Sorin, Carmen (Studies in Natural Language and Linguistic Theory, 2012)
This volume explores the interpretation of indefinites and the constraints on their distribution by paying particular attention to key issues in the interface between syntax and semantics: the relation between the semantic properties of indefinite determiners and the denotation of indefinite DPs, their scope, and their behaviour in generic and conditional sentences. Examples come from French, other Romance languages and English. Central to the proposed analyses is a distinction between two types of entities, individualized entities and amounts. Weak indefinites are analyzed as existential generalized quantifiers over amounts and strong indefinites as either Skolem terms or generalized quantifiers over individualized entities. The up-to-date review of the literature and the new falsifiable proposals contained in this book will be of particular interest to linguistics students and scholars interested in the cross-linguistic semantics of indefinites.